2004
DOI: 10.1161/01.cir.0000109642.27985.fa
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Overexpression of Noncleavable and Secreted Forms of Tumor Necrosis Factor Provokes Disparate Cardiac Phenotypes

Abstract: Background-Recent studies suggest that posttranslation processing or "shedding" (ie, secretion) of tumor necrosis factor (TNF) by tumor necrosis factor-␣ converting enzyme (TACE) may contribute to the left ventricular (LV) remodeling that occurs in the failing human heart. Methods and Results-To address the functional significance of TNF shedding, we generated lines of transgenic mice with targeted overexpression of secreted wild-type (MHCsTNF 2 ) TNF and overexpression of a mutated noncleavable transmembrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 17 publications
3
58
2
1
Order By: Relevance
“…In any way, an overall outcome of glutathione repletion is the disruption of the TNF-α/ TNF-R1/ N-SMase signalling cycle. In fact, the effects of NAC treatment resemble those provided by TNF-α or TNF-R1 ablation, opposite to the deleterious effects brought by sTNF-α overexpression [48]. Thus, ablation of TNF-R1 or TNF-α in mice leads to a better post-MI preservation of the cardiac function compared with post-MI WT mice [49,50].…”
Section: Discussionmentioning
confidence: 93%
“…In any way, an overall outcome of glutathione repletion is the disruption of the TNF-α/ TNF-R1/ N-SMase signalling cycle. In fact, the effects of NAC treatment resemble those provided by TNF-α or TNF-R1 ablation, opposite to the deleterious effects brought by sTNF-α overexpression [48]. Thus, ablation of TNF-R1 or TNF-α in mice leads to a better post-MI preservation of the cardiac function compared with post-MI WT mice [49,50].…”
Section: Discussionmentioning
confidence: 93%
“…Further research demonstrated that the myocardial ECM maintains alignment of myofibrils within the myocyte through a collagen-integrincytoskeleton-myofibril relation (50,132,254,365,367,395,398,441). In addition to a fibrillar collagen network, a basement membrane, proteoglycans, and glycosaminoglycans, the myocardial ECM contains a large reservoir of bioactive molecules (17,34,41,64,89,95,101,109,111,114,188,288,360,362,492). For example, it has been demonstrated that the concentration of bioactive signaling molecules such as angiotensin II (ANG II) and endothelin (ET)-1 are over 100-fold higher within the myocardial interstitium than in plasma (89,101,288,492).…”
Section: A Structure and Function Of The Myocardial Matrixmentioning
confidence: 99%
“…For example, it has been demonstrated that the concentration of bioactive signaling molecules such as angiotensin II (ANG II) and endothelin (ET)-1 are over 100-fold higher within the myocardial interstitium than in plasma (89,101,288,492). Moreover, cytokine activation and signaling such as that for tumor necrosis factor-␣ (TNF) is highly compartmentalized within the myocardial interstitium (95,111). Growth factors such as transforming growth factor-␤ (TGF) are stored in a latent form within the myocardial interstitium and thereby form a reservoir of signaling molecules that directly influence myocardial ECM synthesis and degradation (67,82,218,298,399,443).…”
Section: A Structure and Function Of The Myocardial Matrixmentioning
confidence: 99%
“…Membranebound and cleaved TNF have distinct physiological effects as demonstrated in models of heart disease, arthritis, and systemic shock (3)(4)(5). Biochemically, p75/TNFRSF1B is more easily activated by membrane-bound TNF, whereas p55/TNFRSF1A readily responds to soluble TNF (5).…”
mentioning
confidence: 99%